A feature based analysis of Igbo complementisers (2019)
"It has been argued that Igbo complementisers are associated with more than one clause type and therefore, cannot be classified based on the type of clause they introduce. This assertion has not been further examined in Igbo as the paucity of studies on Igbo complementisers show. Hence, there is need to characterise Igbo complementisers based on features for the purpose of classification. This study, therefore, re-examines the syntax of Igbo complementisers with a view to determining their distribution and c-selection properties as well as distinguish them based on their features. Data for the study were gathered from primary and secondary sources. The study identified three main complementisers in Igbo. They are nà ‘that’, mà ‘if/whether’ and kà ‘that’. ‘na’ c-selects mostly embedded declarative clauses. ‘mà introduces mostly interrogative clauses where both the matrix and embedded clauses bear overt question morpheme, while ‘kà’ is the only complementiser that introduces subjunctive clauses. Based on their behaviours, the study posits that ‘na’ ‘‘mà and ‘kà’ have strong declarative, interrogative and subjunctive features respectively. Using distinctive feature matrix, the study characterised and distinguished Igbo complementiser. It was also observed that there is no agreement between complementiser and inflection as obtainable in English since Igbo complementisers are not specified for any tense that matches with that of the c-selected IP. The study concludes that Igbo complementisers can be classified using distinctive features.